ANALISIS KESENJANGAN REGULASI DAN FAKTA DALAM PENGADAAN PERPUSTAKAAN KHUSUS DI KANTOR WILAYAH KEMENTRIAN AGAMA PROVINSI SUMATERA BARAT - Puspita, Nadila; Marlini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the management of the special library at the Regional Office of the Ministry of Religious Affairs in West Sumatra, based on the National Library Regulation No. 7 of 2022, which clearly establishes standards for the implementation of special libraries. The findings reveal a gap between regulation and practice. Using a qualitative method, the research shows that the special library does not have a dedicated room, is merged with the office of Islamic extension staff, and is not managed by professional librarians. In addition, inconsistencies in informants’ responses indicate weak internal communication and limited understanding of regulations. These conditions demonstrate that the special library has not been prioritized by the institution, resulting in ineffective information services. The study concludes that policy evaluation, provision of a dedicated library space, and appointment of specialized staff are necessary to ensure that the special library functions in accordance with regulations and supports institutional performance